Patterns and Mechanisms of Social Support in Reducing Preoperative Anxiety: A Scoping Review - Nurfadillah Nurfadillah; Sri Wahyuningsih; Andi Fitrah Ramadhanty; Nurhidayat Tanam Hadi Kisworo (Universitas Wiralodra, 2025)
Preoperative anxiety is a common psychological problem experienced by surgical patients and may affect both physical and psychological readiness prior to surgery. Various nursing interventions and forms of social support have been developed to reduce preoperative anxiety; however, the scientific evidence regarding their patterns and underlying mechanisms remains fragmented. This study aimed to map the forms of social support, nursing interventions, and mechanisms involved in reducing preoperative anxiety among surgical patients. A scoping review methodology was employed, involving a literature search across four electronic databases. Articles that met the inclusion criteria were analyzed and mapped using a charting table covering study objectives, types of interventions or social support, underlying mechanisms, and reported outcomes. A total of 20 articles were included in this review. The findings indicate that informational support through preoperative education, emotional and professional support from healthcare providers, and non-pharmacological interventions such as breathing relaxation techniques and spiritual approaches play a significant role in reducing preoperative anxiety. The identified mechanisms include reduced uncertainty, enhanced psychological coping, and regulation of physiological stress responses. This scoping review highlights the importance of a holistic nursing approach in preoperative care and provides a foundation for the development of evidence-based interventions to improve the quality of care for surgical patients.